The influence of personal hobby on personality of nursing students in UiTM Sarawak / Muhammad Faisal Rosian ... [et. al] - Rosian, Muhammad Faisal; Abang Yusuf, Abang Zulkemain; Mustafa, Mohd Fikri; Yaacob, Nor Izat (2008)
Hobbies are practiced for interest and enjoyment, rather than financial reward. Examples include collecting, creative, and artistic pursuits, making, tinkering, sports and adult education. Engaging in a hobby can lead to acquiring substantial skill, knowledge and experience. However, personal fulfillment is the aim. What are hobbies for some people are professions for others: a chef may enjoy cooking as a hobby, while a professional game tester might enjoy playing computer games. Generally speaking, the person who does something for fun, not remuneration, is called an amateur, as a distinct from a professional.